Multivariate Granger Causality between Electricity Generation, Exports, Prices and Economic Growth in Turkey - Altıntas, Halil; Kum, Melike (International Journal of Energy Economics and Policy, 2013)
This study is the first employing annual data for Turkey from 1970 to 2010 to examine the short and long-run causal relationship between economic growth, electricity generation, exports and prices in a multivariate model. According to the bounds test results, when electricity generation and economic growth are the dependent variable there are two cointegrating relationships. According to the results, long-run equilibrium relationship and long-term causality are found between economic growth, electricity generation, export and price. Hence, in the short-run, there are bi-directional causalities between economic growth- electricity generation, economic growth-export and electricity generation-export with feedback effect. Keywords: Electricity generation; economic growth; bounds testing; Granger causality; Turkey. JEL Classifications: O4; Q4